Visible Light-catalyzed Fluoroalkylation Reactions of Free Aniline Derivatives - Lantaño, Beatriz (2021)
The electron-rich nature of aminoaromatic compounds and the electrophilic characterof fluoroalkyl R F radicals allow for a special match in substitution reactions. Weherein present visible light-photocatalyzed fluoroalkylation reactions of anilinederivatives, with a study of the reaction mechanisms. The examples evaluated makeuse of different photocatalysts, such as polypyridyl complexes of Ir or Ru transitionmetals, organic dyes such as Rose Bengal, phthalocyanine-metal organocatalysts, orvisible-light activated complexes. Different visible light sources that span from the blueregion of the electromagnetic spectrum to low power red light irradiation sourcesdeliver the excited photocatalysts that ensue into the production of fluoroalkyl R Fradicals. In turn, many sources of R F radicals can be employed, such as fluoroalkylhalides, Togni s reagents, Umemoto s reagent, etc. All these protocol variantsdemonstrate the expansion of the methodology and the versatility of photocatalytictechniques applied to a special family of organic compounds such as aminoaromaticsubstrates, which has been studied by different groups. Contributions from our ownlaboratory will be given.